2016
DOI: 10.18520/cs/v110/i11/2160-2165
|View full text |Cite
|
Sign up to set email alerts
|

Teak (<i>Tectona grandis</i> L.F.):A Preferred Timber for Shipbuilding in India as Evidenced from Shipwrecks

Abstract: One of the greatest achievements of man is the design and development of a variety of watercraft suitable for marine and riverine purposes and safer for the environment. From ancient times, timber was the main component for the construction of these crafts, until it was replaced by iron/steel. As the size of the vessels increased to accommodate more cargo and overseas trade became more frequent, superior quality timber was used in the construction of vessels. Among the timbers used, teak was mostly preferred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Teak has been harvested for centuries to produce high-quality, durable, and fancy decorative timber as a raw material for art and jewelry [68], handicraft and wood carving [69,70], carpentry [71], traditional household items [72], furniture [73][74][75][76][77][78][79], architectural buildings and construction [80][81][82], and shipbuilding [83] because of its inherent natural desirable characteristics (i.e., lightweight but high strength and hardness, dimensional stability, natural durability, straight grain and easily woodworking, and beautiful artistic appearance). Teak is a tree species that produces one of the most valuable premium timbers all around the globe.…”
Section: Community's Teak Plantationmentioning
confidence: 99%
“…Teak has been harvested for centuries to produce high-quality, durable, and fancy decorative timber as a raw material for art and jewelry [68], handicraft and wood carving [69,70], carpentry [71], traditional household items [72], furniture [73][74][75][76][77][78][79], architectural buildings and construction [80][81][82], and shipbuilding [83] because of its inherent natural desirable characteristics (i.e., lightweight but high strength and hardness, dimensional stability, natural durability, straight grain and easily woodworking, and beautiful artistic appearance). Teak is a tree species that produces one of the most valuable premium timbers all around the globe.…”
Section: Community's Teak Plantationmentioning
confidence: 99%
“…According to Sen et al (2009) and Muller 2010 the presence of several different natural substances such as resinous materials, gummy depositions, oils, alkaloids, silica, etc. Recently, the anatomical analyses of shipwrecks found in the west central coast of India, have indicated that the wood of "teca" (Tectona grandis L.f.) has been largely used by Indians and others shipbuilders, mainly due to specifical timber properties, such as moderate basic density, high mechanical resistance, high dimensional stability and few defects during drying wood; to contain silica and resinous oils, conferring resistance to the attack by marine xylophages like "turu" (Teredo navalis) and also because it has high resistance to decomposition in terrestrial conditions (Tripati et al 2005(Tripati et al , 2016a(Tripati et al , 2016b. Maineri & Chimelo (1989) the woods of C. villosum and A. leiocarpa, used more frequently on the se regional boats, have good resistance to attacks by xylophages' organisms, being preferably indicated for naval construction, mainly for structural parts of the boats that are in contact with water, thus being more susceptible to attack by aquatic xylophages.…”
Section: Speciementioning
confidence: 99%
“…5 Teak has long been a preferred wood for shipbuilding in India. For more on teak timber in Indian ships, see "Use of Timber in Shipbuilding Industry" (Tripati, Sujatha, Rao, and Satyanarayana Rao 2005). desire for overseas political and economic exploits was already depleting oak forests.…”
Section: Enfield-teak Negotiationsmentioning
confidence: 99%